Two Distinct Pathways in Mice Generate Antinuclear Antigen-Reactive B Cell Repertoires - Faderl, Martin; Klein, Fabian; Wirz, Oliver F.; Heiler, Stefan; Albertí-Servera, Llucia; Engdahl, Corinne; Andersson, Jan; Rolink, Antonius (Frontiers in Immunology, 2018)
The escape of anti-self B cells from tolerance mechanisms like clonal deletion, receptor editing and anergy results in the production of autoantibodies, which is a hallmark of many autoimmune disorders. In this study we demonstrate that both germline sequences and somatic mutations contribute to autospecificity of B cell clones. For this issue, we investigated the development of anti-nuclear autoantibodies (ANAs) and their repertoire in two different mouse models. First, in aging mice which were shown to gain several autoimmune features over time including ANAs. Second, in mice undergoing a chronic graft-versus-host disease (GVHD), thereby developing SLE-like symptoms. Detailed repertoire analysis revealed that somatic hypermutations were present in all Vh and practically all Vl regions of ANAs generated in these two models. The ANA B cell repertoire in aging mice was restricted, dominated by clonally related Vh1-26/Vk4-74 antibodies. In the collection of GVHD derived ANAs the repertoire was less restricted but the usage of the Vh1-26/Vk4-74 combination was still apparent. Germline conversion showed that the somatic hypermutations in the 4-74 light chain are deterministic for autoreactivity. Detailed analysis revealed that anti-nuclear reactivity of these antibodies could be induced by a single amino acid substitution in the CDR1 of the Vk4-74. In both old B6 and young GVHD mice, conversion of the somatic mutations in the Vh and Vl regions of non Vh1-26/Vk4-74 using antibodies showed that B cells with a germline encoded V gene could also contribute to the ANA reactive B cell repertoire. These findings indicate that two distinct pathways generate ANA producing B cells in both model systems. In one pathway they are generated by Vh1-26/Vk4-74 expressing B cells in the course of immune responses to an antigen that is neither a nuclear antigen nor any other self-antigen. In the other pathway, ANA producing B cells are derived from progenitors in the bone marrow that express B-cell receptors (BCRs) which bind to nuclear antigens and that escape tolerance induction, possibly as a result of crosslinking of their BCRs by multivalent determinants of nuclear antigens.